Exploring effects of betaine-homocysteine methyltransferase (BHMT) gene polymorphisms on fatty acid traits and cholesterol in sheep - J. P. Munyaneza; A. Gunawan; R. R. Noor (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study was aimed to explore the effects of Betaine-Homocysteine Methyltransferase (BHMT) gene polymorphisms on fatty acid traits and cholesterol in lambs. This study used a total of 147 blood samples for genotyping including 19 Javanese Fat-Tailed (JFT), 16 Javanese Thin-Tailed (JTT), 41 Composite Garut (CG), 35 Compass Agrinak (CA) and 36 Barbados Black Belly Cross (BC). A total of 61 rams as representative from five breed of sheep were selected for association study. Identification of BHMT single nucleotide polymorphisms was analyzed by PCR-RFLP method. Association of BHMT genotypes with fatty acid traits and cholesterol was performed by T-TEST. BHMT genotyping resulted into three genotypes (CC, CT and TT). Gene frequency of BHMT (g. 9947372 C>T) was in Hardy-Weinberg Equilibrium, excluding Javanese Fat-Tailed sheep. Association of BHMT genotypes with fatty acid traits resulted into a significant association (P<0.05) with C14:1, C17:1 and C18:0 fatty acids but not with cholesterol in sheep. SNP g. 9947372 (C>T) of BHMT gene might be a useful marker for selecting and producing sheep meat with desirable fatty acids.